How to Deal with the Verses of War: Abdullah Saeed’s Instructional Values on Reading the Qur’an - Akhmad Siddiq (Universitas Islam Negeri Mataram, 2021)
The connection between violence and religious principle from time to time has been an essential topic discussed among Muslim scholars. Many radical movements, such as the Islamic State of Iraq and Syiria (ISIS), referred to the Qur’an and hadith for justifying or rationalizing their violent acts. They consumed the verses of the Qur’an in order to graps and spread their mission. They hijacked the scripture in their behalf. This article aims to describe the verses of war in the Qur’an which structurally consists of social and political nuances. This article also discusses what so-called “permissive-structure” or “instruction-structure” and elucidates several verses of war, based on Tafsīr al-Qur’ān al-‘Aẓīm written by Imam al-Ḥāfiẓ Abū al-Fidā’ and al-Mīzān fī Tafsīr al-Qur’ān written by Sayyid Muḥammad Ḥusayn al-Ṭabāṭabā’ī. Using hermeneutical approach and discourse-analysis, this study argues that the verses of war in the Qur’an have been contextually misinterpreted by the radical groups to achieve their political interests.